Efficient Solar-Powered Bioremediation of Hexavalent Chromium in Contaminated Waters by Chlorella sp. MQ-1 - Zhou, Tiancheng; Xie, Zhangzhang; Jiang, Xinyu; Zou, Xiangbo; Cheng, Jiong; Chen, Chuangting; Kuang, Cao; Ye, Ji; Wang, Ying; Liu, Fanghua (Water (Basel), 2024)
Microalgae are known for their efficient removal of hexavalent chromium (Cr(VI)) through biosorption and bioaccumulation, yet the subsequent release of Cr(VI) upon cell death remains a challenge. The reduction of Cr(VI) to the less toxic trivalent chromium [Cr(III)] is another critical remediation strategy that mitigates the risk of Cr(VI) re-release, but research on microalgal reduction of Cr(VI) is scarce. In this study, a microalgal strain designated as MQ-1 was isolated from chromium-contaminated mine effluent, demonstrating the capability to tolerate and remove Cr(VI). Phylogenetic analysis revealed that MQ-1 is closely related to the genus Chlorella; hence, it is classified as Chlorella sp. MQ-1. This strain exhibited robust growth at Cr(VI) concentrations below 2 mg/L, achieving a removal rate higher than 82% for initial Cr(VI) concentrations between 0.5 and 1 mg/L after a 5-day incubation period. Mechanistic studies revealed that MQ-1 promoted the removal of Cr(VI) mainly through intracellular bioreduction and bioaccumulation processes, in which more than 60% of Cr(VI) was reduced to the less toxic Cr(III) and stocked in the cells. A two-stage cultivation strategy, involving initial biomass accumulation followed by Cr(VI) treatment, significantly enhanced the removal efficiency, which was further accelerated under illuminated conditions. Notably, MQ-1 cultures with initial OD680 values of 4 and 6 accomplished 84.28% and 91.31% Cr(VI) removal from 2 mg/L solutions, respectively, within 30 hours under light exposure. These findings highlight the potential of MQ-1 to utilize renewable solar energy to reduce Cr(VI) and to mitigate the risk of its re-release into the environment. This characteristic positions MQ-1 as a potentially sustainable and cost-effective solution for Cr(VI) remediation and suggests its significant potential for large-scale implementation in bioremediation strategies aimed at Cr(VI)-contaminated waters.